Bacterial Profiles and Antibiotic Resistance in Chronic Obstructive Pulmonary Disease Patients with Exacerbation and Type 2 Respiratory Failure at Adam Malik General Hospital - Annisa, Lia Mutia; Syarani, Fajrinur; Pradana, Andika; Mutiara, Erna (Folia Medica Indonesiana, 2024)
Highlights: 1. This study provides a comprehensive analysis of various factors such as age, sex, education, occupation, BMI, and comorbidities, and their relationship with bacterial infections in COPD patients experiencing exacerbation and type 2 respiratory failure. 2. While the COPD patients experiencing exacerbation did not exhibit resistance to linezolid and vancomycin, they demonstrated specific antibiotic resistance patterns characterized by high resistance rates to commonly used antibiotics such as meropenem and amikacin. 3. The findings enhance the understanding of the complex interplay of factors influencing infection patterns in this patient population. Abstract Chronic obstructive pulmonary disease (COPD) is a prevalent condition characterized by persistent respiratory symptoms and airflow limitation. Bacterial infections may trigger COPD exacerbations, leading to more severe symptoms as well as increased morbidity and mortality rates. This study aimed to investigate the bacterial profiles and antibiotic resistance in COPD patients who had experienced exacerbation and type 2 respiratory failure at Adam Malik Central General Hospital, Medan, Indonesia. This retrospective study utilized medical records spanning from January 1, 2020, to December 1, 2022. The sample included patients aged 40–90 years who had experienced COPD exacerbation and type 2 respiratory failure. The exclusion criteria were patients who had received antibiotic therapy within 48 hours before admission, were severely immunocompromised, and had severe malignancy. The analysis results were presented in the form of means, standard deviations, and frequency distributions. Additionally, an analysis of the relationship between the categorical variables was performed using the Chi-squared test (p<0.05). The study analyzed 25 subjects with an average age of 63.6 years, primarily consisting of men (84%). It was shown that severe exacerbations were prevalent (92%), accompanied by the presence of common comorbidities including pneumonia (52%), diabetes mellitus (32%), and other non-communicable diseases (44%). Bacterial growth was observed in 76% of the subjects, predominantly involving Gram-negative bacteria (89.4%). Klebsiella pneumoniae (26.3%) and Pseudomonas aeruginosa (21.1%) were the most frequently isolated species. The antibiotic resistance patterns indicated that meropenem and amikacin had the highest resistance rates (100%). Cefepime, ertapenem, and gentamicin exhibited notable resistance rates of 66.7%, 66.7%, and 75.0%, respectively. This study highlights the high prevalence of Gram-negative bacteria and significant antibiotic resistance in COPD patients who exhibit exacerbation and type 2 respiratory failure.